Grass Carp (Ctenopharyngodon idellus) NIMA-Related Kinase 6 Blocks dsRNA-Induced IFN I Response by Targeting IRF3 - Xu, Xiaowen; Li, Meifeng; Deng, Zeyuan; Hu, Jihuan; Jiang, Zeyin; Liu, Yapeng; Chang, Kaile; Hu, Chengyu (Frontiers in Immunology, 2021)
Accumulating evidence indicates that mammalian NIMA (never in mitosis, gene A)-related kinase 6 (NEK6) plays potential roles during the course of tumorigenesis, but little is known about NEK6 in lower vertebrates. Herein, we reported a mammalian ortholog of NEK6 in grass carp (Ctenopharyngodon idellus) (CiNEK6). Multiple alignment of amino acid sequences and phylogenetic analysis showed that CiNEK6 shares a high level of sequence similarity with its counterparts in birds. CiNEK6 was ubiquitously expressed in all tested tissues, and its expression level was increased under treatment with GCRV (dsRNA virus) or poly I:C (dsRNA analogue). Q-PCR and dual-luciferase assays suggested that CiNEK6 overexpression suppressed IFN I activity in CIK cells treated with poly I:C. Knockdown of CiNEK6 resulted in a higher level of IFN I expression in CIK cells treated with poly I:C compared to those which received PBS. Interestingly, analysis of subcellular localization demonstrated that CiNEK6 protein scattered throughout the cytoplasm is gradually congregated together at the edges of karyotheca upon stimulation with poly I:C. Co-IP and co-localization assays suggested that CiNEK6 interacts with CiIRF3 after poly I:C challenge. In poly I:C-treated cells, the phosphorylation of CiIRF3 was increased by CiNEK6 knockdown, but was suppressed by CiNEK6 overexpression, suggesting that CiNEK6 decreases IFN I expression through inhibiting CiIRF3 activity. Cell viability assay, crystal violet staining and detection of Vp5 also showed that CiNEK6 plays an inhibitory role in IRF3-mediated antiviral responses.